Myxobolus spp. (Cnidaria: Myxobolidae) in the circulating blood of fishes from Goiás and Mato Grosso States, Brazil: case report - Úngari, L. P. [UNESP]; Vieira, D. H. M. D. [UNESP]; Santos, A. L. Q.; Silva, R. J. Da [UNESP]; O’dwyer, L. H. [UNESP] (Instituto Internacional de Ecologia, 2021)
Myxosporidiosis is an infectious disease caused by myxozoans of the Phylum Cnidaria, Class Myxosporea, and Order Bivalvulida, considered a common parasite in fresh and saltwater fishes that parasitize many organs, especially gills. In the present study, 49 specimens of fishes belonging to eight genera: Tetragonopterus, Leporinus, Myleus, Pirinampus, Rhapiodon, Pygocentrus, Ageneiosus, and Serrasalmus were collected and blood smears were made, fixed with absolute methanol, and stained with Giemsa 10% to survey hemoparasites. However, myxospores were found in the circulating blood of five (10.20%) fishes belonging to genus Tetragonopterus, Myleus, and Pygocentrus. Two morphological types of Myxobolus spp. were identified in all the five fish specimens analyzed. Usually, investigations on myxozoans in fish are carried out with the search for plasmodia or cysts in the fish organs and observation of the cavity of organs. Nevertheless, this study highlights the importance of also examining the blood of these animals, since these parasites can cause severe pathogenic diseases in fish. Thus, the blood analyses can proportionate preventive sanitary control for commercial fish avoiding economic loss.

A mixosporidiose é considerada uma doença infecciosa causada por mixozoários pertentences ao Filo Cnidaria, Classe Myxosporea e Ordem Bivalvulida, considerados parasitos comuns de peixes de água doce e salgada, parasitando vários órgãos, principalmente as brânquias. No presente estudo, 49 espécimes de peixes pertencentes a oito gêneros: Tetragonopterus, Leporinus, Myleus, Pirinampus, Rhapiodon, Pygocentrus, Ageneiosus and Serrasalmus foram coletados e extensões sanguíneas foram feitas com a finalidade de encontrar hemoparasitos. Entretanto, mixoesporos foram observados em cinco (10.20%) espécimes de peixes, pertencentes aos gêneros Tetragonopterus, Myleus e Pygocentrus. Dois morfotipos de Myxobolus spp. foram identificados parasitando esses peixes. Normalmente, as investigações sobre mixozoários em peixes é realizada com a procura de plasmódios ou cistos nos órgãos dos peixes e observação da cavidade de órgãos. Porém, esse trabalho ressalta a importância de se examinar também o sangue desses animais, já que esses parasitos podem ocasionar patogenias severas em peixes. Sendo assim, a análise sanguínea pode proporcionar controle sanatório preventivo para peixes comerciais e evitar perdas econômicas.
Myxobolus spp. (Cnidaria: Myxobolidae) no sangue circulante de peixes dos estados de Goiás e Mato Grosso, Brasil: relato de caso
Keywords: Morphology; Myleus; Pygocentrus; Tetragonopterus; occurrence; Morfologia; Myleus; Pygocentrus; Tetragonopterus; ocorrência